Paintings That Did Not Become Icons: Pictorial Art in Dostoevsky’s Novels The Insulted and The Injured and The Adolescent - Tatyana A. Kasatkina (Studia Litterarum)
Dostoevsky’s philosophy and theology cannot be extracted from his work in the form of explicit statements; instead, they manifest themselves via a complexly structured figurative text; the author’s strategy consists in stepping back in order to implicitly involve the reader in a process of personal discoveries and personal change. This article focuses on philosophical and theological thoughts in Dostoevsky’s works that are associated with the narratives about paintings which the artist paints against the client’s demand to explicitly express their spiritual meaning. This kind of storyline recurs at least twice in Dostoevsky’s works and appears to be highly effective from a philosophical and theological point of view. In the novel The Insulted and the Injured, it demonstrates what happens “on the other side” of the icon, while in The Adolescent, it serves to reveal the images of the spiritual world in their everyday array and to teach the reader to recognize these images not only within the fictional world of the text but also without, in the external world with which she interacts.